PERSONAL HYGIENE KARYAWAN FOOD AND BEVERAGE TAMAN POETI DAIMA PADANG - Dianti, Weni; Silfeni, Silfeni; Pramudia, Heru (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This study aimed to describe the personal hygiene of food and beverage employees Poeti Taman Padang Daima terms of: personal hygiene (personal cleanliness), general health (general health and fitness), Uniform Chef. This type of research is descriptive with qualitative data. Techniques of collecting data using interviews, observation, and documentation.Â The final conclusion is that personal cleanliness from only 57% of the informants did shower twice a day in a clean before and after leaving for work, 42% of bathing performed once per day for overtime resulting return is late.General health and fitness that 28.5% of employees Taman Padang Poeti Daima sleep seven hours a day, 42.8% slept five hours a day, 28.5% sleep six hours a day. Uniform Chef indicators Aprons Whereas 50% of employees Taman Padang Poeti Daima work using Aprons and 50% work using Aprons when there is oversight of the leadership. Â Key Word : Personal Hygiene and Food And Beverage Employee